2014
DOI: 10.2478/aut-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

A Wear Geometry Model of Plain Woven Fabric Composites

Abstract: The paper g describes a model meant for analysis of the wear geometry of plain woven fabric composites. The referred model consists of a mathematical description of plain woven fabric based on Peirce’s model coupled with a stratified method for the solution of the wear geometry. The evolutions of the wear area ratio of weft yarn, warp yarn and matrix resin on the worn surface are simulated by MatLab software in combination of warp and weft yarn diameters, warp and weft yarn-to-yarn distances, fabric structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…area ratio on the worn surface. Hence, in this paper, the components' area ratio on the worn surface of the PTFE/Kevlar twill fabric was analyzed by the wear experiment and by the theoretical calculations with our previous wear geometry model [17]. The wear process and behavior of the PTFE/Kevlar twill fabric were investigated under dry sliding conditions against AISI 1045 steel by using a ring-on-plate tribometer.…”
Section: Polytetrafluoroethylene (Ptfe)/kevlar Fabric or Fabric Compomentioning
confidence: 99%
See 3 more Smart Citations
“…area ratio on the worn surface. Hence, in this paper, the components' area ratio on the worn surface of the PTFE/Kevlar twill fabric was analyzed by the wear experiment and by the theoretical calculations with our previous wear geometry model [17]. The wear process and behavior of the PTFE/Kevlar twill fabric were investigated under dry sliding conditions against AISI 1045 steel by using a ring-on-plate tribometer.…”
Section: Polytetrafluoroethylene (Ptfe)/kevlar Fabric or Fabric Compomentioning
confidence: 99%
“…Recently, it has been demonstrated that the textile structures, such as weaves [14,15] and weft densities [16], showed an important impact on the wear performance of such materials. However, even without considering the influence of the resin matrix, surface treatment, filling of particles, weaves, and so on, just for a specific structure fabric, which we could consider as a two-component (weft and warp) material system, textile structures will make the components' distribution of such materials uneven [17]. As shown in Figure 1, by taking a horizontal section, the wear geometry of warp and weft changes with the section height, which can be equivalently expressed as the wear depth (To distinguish clearly, the color of the wear geometry is different from the yarns intentionally).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of these creates a single composite with excellent tribological properties. Moreover, using woven composites, one can also easily manufacture a complexshaped material, which can be used in many industries [9][10][11]. During the fabrication of complex shapes, the main requirement is avoiding the wrinkling of the reinforcement material during composite preparation because wrinkling decreases the mechanical quality during various applications [12].…”
Section: Introductionmentioning
confidence: 99%